A risk-stratified model for predicting endometrial atypical hyperplasia and cancer to guide biopsy decisions in asymptomatic postmenopausal women - Wu, Shanshan; Zhang, Xu; Lai, Suhan; Yang, Xiaohui; Wan, Jing (Frontiers in Medicine, 2025)
BackgroundEndometrial atypical hyperplasia (EAH) and endometrial cancer (EC) are increasingly detected in asymptomatic postmenopausal women. This often leads to delayed treatment. Risk stratification remains challenging, and single-factor models may not accurately identify high-risk individuals. This study aimed to develop and validate a multivariable prediction model for identifying EAH or EC in asymptomatic postmenopausal women.MethodsThis retrospective cohort study included asymptomatic postmenopausal women with endometrial pathology records from the Third Affiliated Hospital of Sun Yat-sen University, China (2021–2024). Candidate risk factors included demographics, clinical characteristics, and hematological parameters. The primary outcome was a composite of histologically-confirmed EAH or EC. Multivariable Poisson regression with robust variance was then employed to identify independent risk factors for this composite outcome. Risk - stratified models were developed by calculating predicted probabilities for key combinations of risk factors.ResultsAmong 928 patients [median age: 59 years, IQR (interquartile range): 55–65; median BMI: 23.4 kg/m2], the overall prevalence of EAH and EC was 2.59% (24/928). Key independent risk factors included endometrial thickness (EMT) > 8 mm [vs. ≤ 4 mm: adjusted Relative Risks (aRR) = 11.34, 95% confidence interval (95% CI): 4.35–39.56; p < 0.001], diabetes (aRR = 2.54, 95% CI: 1.12–5.78; p = 0.026), and platelet count per 109/L increase (aRR = 1.01, 95% CI: 1.01–1.02; p < 0.001). EMT > 8 mm was the strongest predictor, with the highest aRR. In the stratified analysis, the combination of EMT > 8 mm and diabetes was associated with the highest observed prevalence (33.33%). The risk-stratified model demonstrated clinical utility: using a ≥ 5% risk threshold, biopsy would be recommended for 17% of patients (sensitivity 70.8%, specificity 84.4%); at a ≥ 10% threshold, biopsy would be recommended for 4.3% of patients (requiring 3.64 biopsies per true positive case).DiscussionThe risk of EAH and EC among asymptomatic postmenopausal women varies significantly based on clinical factors. This risk-stratified modeling approach delivers individualized risk estimates to inform endometrial biopsy decisions, facilitating personalized patient management.